Case report: Immediate revascularization for symptomatic hepatic artery pseudoaneurysm after orthotopic liver transplantation? A case series and literature review - Lerut, An Verena; Pirenne, Jacques; Sainz-Barriga, Mauricio; Blondeel, Joris; Maleux, Geert; Monbaliu, Diethard (Frontiers in Surgery, 2023)
Introduction Hepatic artery pseudoaneurysm (HAPA), a rare vascular complication that can develop after liver transplantation, is associated with a high mortality rate and graft loss. To salvage the liver graft, immediate revascularization, either through surgical or endovascular intervention, is required. However, currently there is no consensus on the optimal strategy. Here, we report three cases of liver transplant recipients diagnosed with HAPA and treated with immediate revascularization. In addition, we present an overview of HAPA cases described in the literature and make recommendations on how to treat this rare complication. Methods All adults transplanted in our center between 2005 and 2021 were retrospectively reviewed. Literature search was done in PubMed for original studies between 1980 and 2021 reporting early hepatic artery (pseudo) aneurysm after liver transplantation requiring either surgical or endovascular intervention. Results From a total of 1,172, 3 liver transplant patients were identified with a symptomatic HAPA and treated with immediate revascularization. HAPA occurred 73, 27, and 8 days after liver transplantation and was treated with immediate revascularization (two surgical and one endovascular intervention). Literature review identified 127 cases of HAPA. HAPA was managed with endovascular therapy in 20 cases and by surgical intervention in 89 cases. Overall reported mortality rate was 39.6%, whereas overall graft survival was 45.2%. Conclusion Immediate surgical or radiological interventional excision and prompt revascularization to salvage liver grafts is feasible but still associated with a high mortality.